Analysis of the influence of brand image and religious belief on purchase intention of halal cosmetic products with attitude as an intervening variable - Firli Dwi Kusuma Putri; Achmad, Nur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study analyzes the influence of Brand Image and Religious Belief on Purchase Intention of halal cosmetic products, with Attitude toward Product as a mediating variable. A quantitative approach is employed, utilizing Partial Least Squares (PLS) for data analysis. The study's population comprises Muslim women in Surakarta who use halal-certified cosmetics, with a sample selected through non-probability purposive sampling. Data collection is conducted via questionnaires using a Likert scale (1–5), and Structural Equation Modeling (SEM) with SmartPLS 4.0 is applied for analysis. The results indicate that Brand Image and Religious Belief do not directly impact Purchase Intention. However, both variables significantly influence Attitude toward Product. Furthermore, Attitude toward Product mediates the relationship between Brand Image and Purchase Intention, as well as between Religious Belief and Purchase Intention. Study limitations include a restricted sample size, limited geographic coverage, and the exclusion of other potential independent variables. Future research should expand the sample size, broaden geographic scope, and incorporate additional independent variables to enhance the validity and generalizability of the findings.